Barriers of Adopting Artificial Intelligence Tools in Engineering Construction Projects - ALKAABI, ABDULLA (2023)
Engineering construction projects using AI technologies create obstacles. Barriers prevent AI integration in construction. Insufficient knowledge and understanding of AI, data management and integration issues, legal and regulatory hurdles, financial considerations, reluctance to change, and interoperability issues all hinder AI system adoption and implementation. First, many engineering and construction specialists may not understand or use artificial intelligence. The situation may cause concern and trepidation about integrating AI technologies and lack understanding of their optimal deployment and operation. Construction data management and integration are difficult. AI algorithms depend on data for training and analysis. AI technologies often struggle with construction data's fragmentation, inconsistency, and confidentiality. AI technologies may also face regulatory and legal hurdles related to data confidentiality, protection, and property rights. These issues may limit AI tool use or increase legal liability, hindering adoption. Integrating AI technology may be costly, especially for smaller companies with limited funds. Hardware, software, and training costs may prevent certain construction businesses from using AI solutions. Industry culture and change aversion may slow AI tool adoption. Conventional attitudes, fear of termination, and reluctance to change processes may hinder AI adoption in construction workflows. Finally, interoperability and integration issues may hinder AI adoption. Incorporating AI into pre-existing software, systems, and processes may require significant effort and tailoring, and compatibility issues may hinder the easy integration of AI utilities into building projects.